2019 13th International Conference on Research Challenges in Information Science (RCIS) 2019
DOI: 10.1109/rcis.2019.8876999
|View full text |Cite
|
Sign up to set email alerts
|

Towards Detecting and Mitigating Conflicts for Privacy and Security Requirements

Abstract: requirement engineering live in a world were contradiction is the norm. Hence, development of software engineering is usually an adjustable and upgrading cyclical process. We found in the literature that some requirements conflict with other requirements. We will focus in this study on identification and resolution of conflicts between security and privacy requirements. Although, most the recent studies focus on identifying conflicts without proposing a solution to resolve it. This paper presents an approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The authors conducted thirteen interviews at six private companies and found nine personal factors that affect how software developers perceive and interpret privacy requirements. Alkubaisy et al [52] proposed a framework to identify and resolve conflicts between security and privacy requirements. The authors use patterns to describe the problem and propose a solution to each conflict encountered by the framework.…”
Section: Rq1 According To the Literature What Are The Methodologiementioning
confidence: 99%
“…The authors conducted thirteen interviews at six private companies and found nine personal factors that affect how software developers perceive and interpret privacy requirements. Alkubaisy et al [52] proposed a framework to identify and resolve conflicts between security and privacy requirements. The authors use patterns to describe the problem and propose a solution to each conflict encountered by the framework.…”
Section: Rq1 According To the Literature What Are The Methodologiementioning
confidence: 99%
“…Some of the steps are semi-automated, while others are manual steps, based on the analyst's point of view. First, the conflicts between requirements are identified, based on a matrix presented by a previous study (Alkubaisy, Cox & Mouratidis, 2019). Hence, we sort the requirements that could lead to a potential conflict.…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…The authors have also cited the work of Alkubaisy, Cox and Mouratidis (2019), who investigate conflicts between security and privacy requirements.…”
Section: Table 23 Comparison Between Conflict Analysis Approachmentioning
confidence: 99%
“…Nevertheless, the idea was considered a successful trial. Furthermore, Alkubaisy et al [14] analyzed the conflict detection between privacy and security requirements. In their approach they tried to simplify the detection by using patterns to describe the problem.…”
Section: Related Studymentioning
confidence: 99%